1976
DOI: 10.1099/0022-1317-32-2-283
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Subviral Components from Transmissible Gastroenteritis Virus

Abstract: SUMMARYExposure of purified transmissible gastroenteritis virus, a porcine coronavirus, to non-ionic detergents resulted in the removal of the surface projections and > 98 % of the virus lipid. Virus RNA was associated with a subviral particle which had a sedimentation coefficient of 65olS, compared with 495 S for the intact virion, and which banded in Cs2SO4 gradients at 1.295 g/ml. Negatively stained preparations of subviral particles were shown by electron microscopy to contain spherical particles of 6o to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…One striking feature common to three of these viruses is the presence of only one nonglycosylated protein, whilst OC43 contains two. In TGEV this protein is probably complexed with the RNA (Garwes et al I976) In a recent publication, Garwes et al (1976) reported the isolation of an RNA-containing subviral particle from NP 4o-treated TGEV. By electron microscopy these particles had a diam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One striking feature common to three of these viruses is the presence of only one nonglycosylated protein, whilst OC43 contains two. In TGEV this protein is probably complexed with the RNA (Garwes et al I976) In a recent publication, Garwes et al (1976) reported the isolation of an RNA-containing subviral particle from NP 4o-treated TGEV. By electron microscopy these particles had a diam.…”
Section: Discussionmentioning
confidence: 99%
“…This paper also reports the isolation of subviral components of HEV using the detergent treatment described by Garwes, Pocock, & Pike (1976) for TGEV and Kennedy & Johnson-Lussenburg (I976) for 229E.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the organization and expression of the TGEV genome (Dennis & Brian, 1982;Hu et al, 1984;Jacobs et al, 1986;Kapke & Brian, 1986;Rasschaert et al, 1987) tend to confirm the findings reported for two other members of the Coronaviridae, murine hepatitis (MH) and avian infectious bronchitis (IB) viruses (see . Three functional classes of polypeptides have been identified in TGEV virions: a nucleocapsid protein, a matrix protein and a peplomer protein forming the characteristic surface projections (Garwes et al, 1976). The peplomer protein E2, a highly glycosylated polypeptide of 200K to 220K, has been shown to elicit the production of neutralizing antibodies Jimenez et al, 1986;Garwes et al, 1987) which are able to confer protection on suckling piglets (Garwes et al, 1978/79).…”
Section: Introductionmentioning
confidence: 99%
“…TGEV contains three major structural polypeptides: the peplomer glycoprotein E2 (200K to 220K), which forms the distinctive surface projections, the transmembrane or matrix protein E 1 (29K + 1K), and the nucleoprotein N (47K + 1K), in which a single infectious RNA molecule of 20 kb or more is embedded (Garwes et al, 1976;Laurie et al, 1986;Brian et al, 1980). In TGEV-infected cells, five species of subgenomic mRNA have been characterized, in vitro translation of which has allowed partial coding assignment (Hu et al, 1984;Jacobs et al, 1986;Rasschaert et at., t987).…”
Section: Introductionmentioning
confidence: 99%